Early maladaptive schemas, depression and anxiety in adolescent psychiatric out-patients - Ahrnberg, Hanna; Lindblom, Jallu; Kaltiala, Riittakerttu; Karukivi, Max (CAMBRIDGE UNIV PRESS, 2026)
Background: A growing number of studies among adolescents have reported early maladaptive schemas (EMS) to associate with anxiety and depression within non-clinical samples. However, there is a gap of knowledge concerning clinical populations.
Aims: The current study's aim was to explore the potential association between EMS domains and anxiety and depressive symptoms within clinical sample of adolescents.
Method: The current study included 176 adolescent psychiatry out-patients. The EMS domains were measured with the Young Schema Questionnaire-Short Form 2-Extended (YSQ). Their association with anxiety symptoms (the Overall Anxiety Severity and Impairment Scale) and depressive symptoms (the Beck Depression Inventory II) were analysed with general linear models while controlling for significant confounding factors.
Results: Depressive symptoms were associated with three of the four EMS domains: Disconnection and Rejection (η2p=0.047, p=0.005), Impaired Autonomy and Performance (η2p=0.074, p<0.001), and Impaired Limits (η2p=0.053, p=0.003). Anxiety symptoms were associated with two EMS domains: Impaired Autonomy and Performance (η2p=0.046, p=0.005) and Excessive Responsibility and Standards (η2p=0.054, p=0.002).
Conclusions: Various EMS domains were associated with depressive and anxiety symptoms among adolescent out-patients. Further studies are needed on the effect of EMSs on the treatment outcomes for depression and anxiety.